Variasi Dosis Mulsa Organik Akasia dan Kirinyuh dalam Mengendalikan Gulma pada Tanaman Kedelai : Studi Karateristik Hasil Tanaman Kedelai - Ramut, Anuar; Harta, Rika Yusli; Pani, Mario; Sitinjak, Lentina; Gunawiati, Tika Puji (AGROSUSTAIN, 2025)
The success of controlling weeds in soybean plantations, apart from being determined by the type, also determines the dose of mulch. This research aims to obtain the type and dosage of organic mulch to control weeds in soybean plantations. The research was carried out from August to December 2024, in Lawe Sagu Hulu Village, Lawe Bulan District, Southeast Aceh Regency, Aceh Province. The types of organic mulch used are: acacia and kirinyuh, and the doses used are: 0; 4.8; 9.6; 14.4 and 19.2 tons ha-1. The design used was a bifactorial randomized block design with 4 replications. The variables observed were: number of pods, number of seeds, seed weight, weight of 100 seeds and dry seed yield. The research results showed that an organic mulch dose of 19.2 tons ha-1 could increase the number of pods, number of seeds, seed weight and dry seed yield. Independently, the type of mulch and the interaction between type and dose had no effect on the observed soybean crop yields.